EXPLORATION OF LIVING QUR'AN IN MATTAMPUNG TRADITION OF THE BUGIS COMMUNITY: A STUDY IN BARUGAE, BONE, SOUTH SULAWESI (International Conference on Social and Islamic Studies, 2021)
This paper examines Mattampung tradition in the Bugis community which is analyzed using the Living Qur'an lens. The Living Qur'an study is a study of the Qur'an but does not rely on its textual side, but on social phenomena that are born related to the presence of the Qur'an in society. Meanwhile, Mattampung tradition is a tombstone planting ceremony as a substitute for the tombstones that are planted when the body is buried. In this tradition, khatam al-Qur'an and tahlil are carried out. This tradition is carried out with the hope that all prayers from the community will reach the person who died so that he is given a quiet place by his side. This study focuses on Barugae village community, Bone, South Sulawesi. The method used is the ethnographic method, which is a qualitative design in which the researcher describes and interprets the same patterns of values, behavior, beliefs and language of a group with the same culture. The results of this study indicate that the implementation of Mattampung tradition is a form of local community reception of the glory of completing the Qur'an and the suggestion to pray for the dead. Khatam al-Qur'an in this tradition occupies a very important position, especially as a complement to the implementation of Mattampung tradition. Thus, this tradition becomes a place for the local community to send prayers and complete the Qur'an with the aim that the reward of the prayer and completion can reach the person who died and can make it easier for him in his next life.